2015
DOI: 10.1002/tal.1218
|View full text |Cite
|
Sign up to set email alerts
|

Hexagrid – hexagonal tube structures for tall buildings: patterns, modeling, and design

Abstract: SUMMARYThis paper provides a first insight on tube configurations based on the hexagonal shape (hexagrid) for tall buildings. The idea is to investigate the mechanical properties of hexagrid to assess their applicability in tall buildings and to compare their potential efficiency to the more popular diagrid systems.For the above purposes, a general homogenization approach has been established for dealing with any structural patterns, and a methodology for characterizing the structural patterns from the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…The maximum response of the structure in each step of scaling is then extracted to draw the IDA diagrams. After analyzing the groups of IDA curves using statistical methods and then comparing the results with hazard analysis limits, the dynamic structural behavior, capacity, and limit state can be known …”
Section: Incremental Dynamic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum response of the structure in each step of scaling is then extracted to draw the IDA diagrams. After analyzing the groups of IDA curves using statistical methods and then comparing the results with hazard analysis limits, the dynamic structural behavior, capacity, and limit state can be known …”
Section: Incremental Dynamic Analysismentioning
confidence: 99%
“…After analyzing the groups of IDA curves using statistical methods and then comparing the results with hazard analysis limits, the dynamic structural behavior, capacity, and limit state can be known. [7,27,28] FIGURE 37 Concrete usage of three structures at different heights. OSSFS: open-web sandwich slab frame-core-tube structure FIGURE 38 Incremental dynamic analysis results of a cassette structure.…”
Section: One-hundred-forty-five-meter Pushover Analysismentioning
confidence: 99%
“…The 83‐story structure has a CFST tubular structure, which starts with hexagrids in the bottom and changes to diagrids from mid‐height to the top of the structure . Montuori et al studied 90‐story hexagrid and diagrid structures, designed to resemble the Sino Steel International Plaza under construction in China (Figure ), with diagonal angle in the range of 31° to 70° and concluded that hexagrids have a smaller lateral stiffness than diagrids.…”
Section: Hexagridsmentioning
confidence: 99%
“…The 83-story structure has a CFST tubular structure, which starts with hexagrids in the bottom and changes to diagrids from mid-height to the top of the structure. [66] Montuori et al [67] studied 90-story hexagrid and diagrid structures, designed to resemble the Sino Steel International Plaza under close automatically according to the sun light. [68] 9 | DIAGRID FOR SUSTAINABLE STRUCTURES Sustainability of structures is a rising concern in design, construction, operation, and renovation of the buildings especially high-rise and super high-rise buildings.…”
Section: Hexagridsmentioning
confidence: 99%
“…Further, a generalization of the concept of structural pattern, or grid, in the tube configuration for tall buildings has been proposed, and a general approach for modeling, analyzing and designing the relevant structural system has been developed for both regular and non regular grids, i.e. diagrid, hexagrid and Voronoi grid [21,22].…”
Section: Structural Efficiency Of Diagrids and Related Research Issuesmentioning
confidence: 99%